ANALISIS KONSEP NILAI HASIL PADA PROYEK PEMBANGUNAN JEMBATAN PENGHUBUNG DESA SAMBI KABUPATEN BOYOLALI MENGGUNAKAN PROGRAM PRIMAVERA 6.0 - Setiono Setiono; Inas Hasna Muthiah; Muji Rifai (Program Studi Teknik Sipil FT UNS, 2025)
Infrastructure in Indonesia is progressing rapidly, especially in terms of increasing toll roads and the number of national airports. In the implementation of construction projects, construction management plays an important role, especially in managing costs and time. The Sambi Village Connecting Bridge as one of the infrastructure development projects also has a crucial role in supporting the economic, social, and cultural sectors in the area. The novelty of this research can be seen in terms of research time, research location, and research object in the form of a bridge. The purpose of this research is to evaluate cost and time forecasts, and determine whether the project will generate profits or losses. In this research, a descriptive analysis method is used which involves collecting, processing, and analyzing data. The concept of earned value was also used to control the cost and time of the project, and was applied through the Primavera 6.0 program. The results of the analysis show that the estimated total project completion time exceeds the planned time, and the use of Primavera 6.0 program can improve the efficiency of the project schedule and cost. In addition, this analysis can also be applied to ongoing projects to evaluate contractor performance. Through this research, recommendations can be drawn to improve the efficiency of project schedules and costs, as well as to evaluate contractor performance on ongoing projects.